Curable resin composition and adhesive composition

By using 58% to 82% of biocurable resin and 18% to 42% of epoxy resin in the curable resin composition and dispersing the core-shell graft copolymer therein by powder phase dispersion method, the solution is solved The environmental pollution and mechanical strength problems of traditional petroleum-based epoxy resins have achieved an efficient and environmentally friendly production process and excellent mechanical properties.

CN119403878APending Publication Date: 2025-02-07LG CHEM LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202480002767.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-01-15
Filing Date
2024-02-01
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The prior art is difficult to replace traditional petroleum-based epoxy resins with environmentally friendly bio-based epoxy resins, reducing environmental pollution, while meeting the mechanical strength characteristics required by traditional epoxy resin compositions, especially when applying powder phase dispersion methods. There are problems of high process costs and difficulty in dispersing.

Method used

The curable resin composition containing 58% to 82% of the biocurable resin and 18% to 42% of the epoxy resin, and the core-shell graft copolymer is dispersed therein by powder phase dispersion method to control grafting. The core content and particle size distribution of the copolymers to improve dispersion efficiency and mechanical properties.

Benefits of technology

The goal of reducing environmental pollution with environmentally friendly bio-based epoxy resins is achieved, while meeting the mechanical strength characteristics required by traditional epoxy resin compositions, and improving productivity and mechanical properties by optimizing process cost and dispersion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005155873080000031
    Figure BDA0005155873080000031
  • Figure BDA0005155873080000071
    Figure BDA0005155873080000071
  • Figure BDA0005155873080000231
    Figure BDA0005155873080000231
Patent Text Reader

Abstract

The present invention relates to a curable resin composition and an adhesive composition comprising the same, the curable resin composition reducing environmental pollution by using an environmentally friendly bio-based epoxy resin instead of a conventional petroleum-based epoxy resin, according to the present invention, all mechanical strength characteristics required by a curable resin composition containing a conventional petroleum-based epoxy resin are satisfied, and the graft copolymer is dispersed in the curable resin by a powder phase dispersion method, thereby having excellent productivity and excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0004] The present invention relates to a curable resin composition and an adhesive composition comprising the curable resin composition as a toughening agent. Background Art

[0005] Curable resins represented by epoxy resins are used in various fields such as electrical and electronic products, automotive parts and building materials. Recently, with the increasing interest in environmentally friendly biomaterials, efforts are being made to apply environmentally friendly biomaterials to epoxy resins. If environmentally friendly bio-based epoxy resins are used to replace traditional petroleum-based epoxy resins, environmental pollution generated during the production of petroleum-based raw materials can be reduced.

[0006] Meanwhile, for the purpose of improving physical properties and processing properties, curable resins such as epoxy resins are used in combination with additives such as inorganic fillers, release agents, and rubber fine particles having rubber-like properties, rather than using curable resins alone. Among them, epoxy resins often exhibit brittleness and require improved impact resistance and bonding strength. This requirement applies not only to traditional petroleum-based epoxy resins, but also to environmentally friendly bio-based epoxy resins.

[0007] As a method for improving the impact resistance of epoxy resin, a method of using a graft copolymer containing a rubbery polymer as an impact reinforcing agent has been proposed. The graft copolymer has a particle form of a core-shell structure including a core containing a rubbery polymer and a shell formed by graft polymerization of the core.

[0008] Here, in order to apply the graft copolymer as an impact reinforcing agent for epoxy resin, the graft copolymer needs to be dispersed in the epoxy resin, and as a method of dispersing the graft copolymer in the epoxy resin, there are a liquid dispersion method and a powder phase dispersion method.

[0009] According to the liquid dispersion method, the graft copolymer is dispersed in the epoxy resin by a stepwise solvent replacement method in which water is replaced with a solvent of a latex-state graft copolymer in which the graft copolymer is dispersed in water, and then the solvent is replaced with the epoxy resin. The liquid dispersion method has the advantage of dispersing the graft copolymer in a uniformly distributed matrix of the epoxy resin, but in order to apply the graft copolymer as an impact enhancer to the epoxy resin, there are problems of storage in which the graft copolymer needs to be kept in a latex state until dispersion, high process costs due to solvent replacement, and environmental problems due to water and solvent discharged respectively during the replacement process of the graft copolymer and the solvent.

[0010] The powder phase dispersion method has the advantage of low process cost, in which a dry powder aggregated from a graft copolymer latex, i.e., a powder phase graft copolymer is directly dispersed in an epoxy resin. However, when the graft copolymer powder is introduced into the epoxy resin, the viscosity of the graft copolymer powder becomes very high, and dispersion becomes very difficult or impossible in practice.

[0011] Therefore, efforts are needed to use environmentally friendly bio-based epoxy resins to replace traditional petroleum-based epoxy resins while satisfying all the mechanical strength properties required of curable resin compositions containing traditional petroleum-based epoxy resins, and to apply powder phase dispersion methods to improve both process costs and environmental aspects in applying impact enhancers to curable resin compositions such as epoxy resins.

[0012] [Prior art literature]

[0013] [Patent Document]

[0014] (Patent Document 1) JP 2006-104328A Summary of the invention

[0015] Technical issues

[0016] The task to be solved by the present invention is to reduce environmental pollution by applying environmentally friendly bio-based epoxy resins to replace traditional petroleum-based epoxy resins, while meeting all the mechanical strength properties required of a curable resin composition containing traditional petroleum-based epoxy resins.

[0017] Furthermore, the task to be solved by the present invention is to apply a powder phase dispersion method to improve both process costs and environmental aspects when applying an impact reinforcing agent to a curable resin composition comprising an environmentally friendly bio-based epoxy resin.

[0018] That is, in order to solve the tasks mentioned in the background technology of the present invention, the purpose of the present invention is to provide a curable resin composition, which uses an environmentally friendly bio-based epoxy resin instead of a conventional petroleum-based epoxy resin, satisfies all the mechanical strength characteristics required of a curable resin composition containing a conventional petroleum-based epoxy resin, and has excellent productivity and excellent mechanical properties by dispersing a graft copolymer in the curable resin through a powder phase dispersion method.

[0019] Furthermore, an object of the present invention is to provide a structural adhesive composition having excellent mechanical strength while containing an environmentally friendly bio-based epoxy resin as a main material by applying the curable resin composition as a toughening agent.

[0020] Technical Solution

[0021] In order to solve the above-mentioned problems, the present invention provides a curable resin composition and an adhesive composition.

[0022] (1) The present invention provides a curable resin composition comprising a continuous phase containing a curable resin and a dispersed phase containing a graft copolymer, wherein the curable resin comprises 58 wt % to 82 wt % of a biocurable resin and 18 wt % to 42 wt % of an epoxy resin, and the graft copolymer is a core-shell type graft copolymer, the core-shell type graft copolymer comprising a core comprising a rubbery polymer and a shell formed by grafting a graft monomer to the rubbery polymer, and the shell has a weight average molecular weight of 10,000 g / mol to 85,000 g / mol.

[0023] (2) The present invention provides the curable resin composition according to (1), wherein the biocurable resin is a bioepoxy resin.

[0024] (3) The present invention provides the curable resin composition according to (1) or (2), wherein the biocurable resin contains an isosorbide unit.

[0025] (4) The present invention provides the curable resin composition according to any one of (1) to (3), wherein the biocurable resin is represented by the following Formula 1.

[0026] [Formula 1]

[0027]

[0028] In formula 1, R 1 and R 2 Each is independently hydrogen, hydroxyl, epoxy or glycidyl, and n is an integer selected from 1 to 1,000.

[0029] (5) The present invention provides a curable resin composition according to any one of (1) to (4), wherein the biocurable resin has an epoxy equivalent weight (EEW) of 150 g / eq to 190 g / eq.

[0030] (6) The present invention provides the curable resin composition according to any one of (1) to (5), wherein the biocurable resin has a viscosity at 25° C. of 500 cPs to 6,000 cPs.

[0031] (7) The present invention provides a curable resin composition according to any one of (1) to (6), wherein the epoxy resin includes one or more selected from bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AD ​​type epoxy resin, bisphenol E type epoxy resin, naphthalene type epoxy resin, biphenyl type epoxy resin, dicyclopentadiene type epoxy resin, phenol novolac type epoxy resin, aliphatic cyclic epoxy resin and glycidylamine type epoxy resin.

[0032] (8) The present invention provides the curable resin composition according to any one of (1) to (7), wherein the epoxy resin has an epoxy equivalent weight (EEW) of 180 g / eq to 190 g / eq.

[0033] (9) The present invention provides the curable resin composition according to any one of (1) to (8), wherein the epoxy resin has a viscosity at 25° C. of 8,000 cPs to 13,500 cPs.

[0034] (10) The present invention provides a curable resin composition according to any one of (1) to (9), wherein the peak area ratio of the biocurable resin to the epoxy resin (biocurable resin:epoxy resin) is 0.60 to 5.60:1, and the peak area ratio is obtained as follows: 0.2 g of the curable resin composition sample is dissolved in acetone, 40 mL of methanol is added thereto, the supernatant is filtered into a 2 mL liquid chromatography vial using a 0.22 μm polytetrafluoroethylene filter, and high performance liquid chromatography (HPLC) is used to detect according to the elution time using an evaporative light scattering detector (ELSD).

[0035] (11) The present invention provides the curable resin composition according to any one of (1) to (10), wherein the rubbery polymer contains one or more monomer units selected from conjugated diene-based monomer units and alkyl acrylate-based monomer units.

[0036] (12) The present invention provides the curable resin composition according to any one of (1) to (11), wherein the core has an average particle diameter of 100 nm to 500 nm.

[0037] (13) The present invention provides the curable resin composition according to any one of (1) to (12), wherein the graft monomer includes an alkyl (meth)acrylate monomer.

[0038] (14) The present invention provides a curable resin composition according to any one of (1) to (13), wherein the grafting monomer includes a methyl (meth)acrylate monomer and an alkyl (meth)acrylate monomer having 2 to 12 carbon atoms.

[0039] (15) The present invention provides the curable resin composition according to any one of (1) to (14), wherein the grafting monomer includes an aromatic vinyl-based monomer.

[0040] (16) The present invention provides a curable resin composition according to any one of (1) to (15), wherein the graft copolymer contains 70% to 92% by weight of a core and 8% to 30% by weight of a shell.

[0041] (17) The present invention provides the curable resin composition according to any one of (1) to (16), wherein the graft copolymer has an average particle diameter of 100 nm to 600 nm.

[0042] (18) The present invention provides a curable resin composition according to any one of (1) to (17), wherein the curable resin composition contains 50% to 99% by weight of a continuous phase and 1% to 50% by weight of a dispersed phase.

[0043] (19) The present invention provides an adhesive composition comprising the curable resin composition according to any one of (1) to (18).

[0044] (20) The present invention provides an adhesive composition according to (19), wherein the adhesive composition comprises a main material, a toughening agent, a polyurethane resin and a curing agent, and the toughening agent is the curable resin composition.

[0045] (21) The present invention provides the adhesive composition according to (20), wherein the main material includes a biocurable resin.

[0046] (22) The present invention provides the adhesive composition according to (21), wherein the main material contains 1 wt % to 40 wt % of a biocurable resin relative to the total content of the adhesive composition.

[0047] (23) The present invention provides an adhesive composition according to any one of (20) to (22), wherein the adhesive composition contains 5 wt % to 32 wt % of a toughening agent relative to the total content of the adhesive composition.

[0048] Beneficial Effects

[0049] The curable resin composition of the present invention reduces environmental pollution by using an environmentally friendly bio-based epoxy resin instead of a traditional petroleum-based epoxy resin, while satisfying all the mechanical strength properties required of a curable resin composition containing a traditional petroleum-based epoxy resin, and has excellent productivity and excellent mechanical properties by dispersing a graft copolymer in the curable resin through a powder phase dispersion method.

[0050] Furthermore, the adhesive composition of the present invention is a structural adhesive composition and has excellent mechanical strength by using a curable resin composition as a toughening agent while containing an environmentally friendly bio-based epoxy resin as a main material. DETAILED DESCRIPTION

[0051] Hereinafter, the present invention will be described in more detail to help understanding of the present invention.

[0052] It should be understood that the words or terms used in the present disclosure and claims should not be understood as the meanings defined in commonly used dictionaries. It will be further understood that, based on the principle that the inventor can appropriately define the meanings of words or terms to best illustrate the invention, the words or terms should be understood as having meanings consistent with their meanings in the technical concept of the present invention.

[0053] The term "monomer unit" used in the present invention may refer to a component, structure or substance itself derived from a monomer, and in particular, may refer to a repeating unit formed in a polymer through the participation of a monomer added to the polymerization reaction during the process of polymerizing the polymer.

[0054] As used herein, the term "composition" includes a mixture of materials including the constituents as well as reaction products and decomposition products formed from the constituent materials.

[0055] The present invention provides a curable resin composition.

[0056] According to one embodiment of the present invention, the curable resin composition may include a biocurable resin as a curable resin and a graft copolymer as an impact reinforcing agent, and in particular, the graft copolymer may be dispersed in the curable resin in a powder form.

[0057] According to one embodiment of the present invention, the curable resin composition may include a continuous phase including a curable resin and a dispersed phase including a graft copolymer, the curable resin may include 58 wt % to 82 wt % of a biocurable resin and 18 wt % to 42 wt % of an epoxy resin, the graft copolymer is a core-shell graft copolymer, which includes a core including a rubbery polymer and a shell formed by grafting a graft monomer to the rubbery polymer, and the shell may have a weight average molecular weight of 10,000 g / mol to 85,000 g / mol.

[0058] According to one embodiment of the present invention, the biocurable resin is an environmentally friendly bio-based curable resin, and may be a curable resin prepared from a bio-based material.

[0059] According to one embodiment of the present invention, the biocurable resin may include derived units from one or more bio-based materials selected from the following: fatty acid oils from plants, isosorbide, furan derivatives, tannin derivatives, terpene derivatives, rosin derivatives, lignin and lignin derivatives. In a specific embodiment, the derived units from the fatty acid oils from plants may be selected from one or more of epoxidized soybean oil units, epoxidized castor oil units, epoxidized linseed oil units, epoxidized canola oil units and epoxidized karanja oil units. In addition, the derived units from furan derivatives may be selected from one or more of the diglycidyl ester units and furfuryl glycidyl ether units of 2,5-furandicarboxylic acid.

[0060] According to one embodiment of the present invention, the biocurable resin may include an isosorbide unit. The isosorbide forming the isosorbide unit is a derivative from sorbitol and corresponds to a bio-based material that can be produced at a low price. In particular, isosorbide can be obtained by dehydration of sorbitan. Sorbitan can be obtained by dehydration of sorbitol, which can be obtained by dehydrogenation of glucose, which can be obtained by depolymerization of polysaccharides such as cellulose and starch.

[0061] According to one embodiment of the present invention, the biocurable resin may be a bioepoxy resin including isosorbide units. In a specific embodiment, the biocurable resin may be a copolymer including isosorbide units and epoxy units, and may be more specifically represented by Formula 1 below.

[0062] [Formula 1]

[0063]

[0064] In formula 1, R 1 and R2 may each independently be hydrogen, hydroxyl, epoxy or glycidyl, and n may be an integer selected from 1 to 1,000. In a specific embodiment, n may be 1 or more, 5 or more, or 10 or more, and 1,000 or less, 900 or less, 800 or less, 700 or less, 600 or less, 500 or less, 400 or less, 300 or less, 200 or less, or 100 or less. In addition, the wavy bonding lines are intended to represent hydrogen, oxygen, R 1 and R 2 The three-dimensional structure of and can correspond to both the solid wedge and the dashed wedge. In a specific embodiment, between the two hydrogen and oxygen and R 2 The wavy bond wires shown in FIG. 1 may have the same orientation, that is, all bond wires may be solid wedges or dashed wedges, and may be in R 1 The wavy bond lines shown in the figure may represent the two hydrogen and oxygen as well as R 2 The stereo orientation is the opposite stereo orientation.

[0065] According to one embodiment of the present invention, the biocurable resin may have an epoxy equivalent weight (EEW) of 150 g / eq to 190 g / eq. In a specific embodiment, the biocurable resin may have an epoxy equivalent weight of 150 g / eq or more, 155 g / eq or more, 160 g / eq or more, or 165 g / eq or more, and 190 g / eq or less, 185 g / eq or less, 180 g / eq or less, 175 g / eq or less, or 170 g / eq or less, and within this range, the effect as a heterogeneous adhesive, particularly as a structural adhesive, may be exhibited.

[0066] According to one embodiment of the present invention, the biocurable resin may have a viscosity of 500 cPs to 6,000 cPs at 25° C. In a specific embodiment, the biocurable resin may have a viscosity of 500 cPs or more, 1,000 cPs or more, 1,500 cPs or more, 2,000 cPs or more, 2,500 cPs or more, or 3,000 cPs or more, and 6,000 cPs or less, 5,500 cPs or less, 5,000 cPs or less, 4,500 cPs or less, 4,000 cPs or less, 3,500 cPs or less, 3,000 cPs or less, 2,500 cPs or less, or 2,000 cPs or less, within which range, due to the low viscosity during mixing of the structural adhesive composition, processability may be further improved.

[0067] According to one embodiment of the present invention, in addition to the biocurable resin, the curable resin may further include other types of curable resins different from the biocurable resin. Here, the other types of curable resins may be epoxy resins, and may specifically include at least two epoxy bonds, and may more specifically be selected from bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol AD ​​type epoxy resins, bisphenol E type epoxy resins, naphthalene type epoxy resins, biphenyl type epoxy resins, dicyclopentadiene type epoxy resins, phenol novolac type epoxy resins, aliphatic cyclic epoxy resins and glycidylamine type epoxy resins One or more.

[0068] According to one embodiment of the present invention, the epoxy resin may have an epoxy equivalent weight (EEW) of 180 to 190 g / eq, and may have a viscosity of 8,000 to 13,500 cPs at 25° C. Within this range, the effect of the structural adhesive may be further improved.

[0069] According to one embodiment of the present invention, the peak area ratio of the biocurable resin to the epoxy resin (biocurable resin: epoxy resin) can be 0.60 to 5.60: 1, wherein the peak area ratio is obtained by dissolving 0.2 g of a curable resin composition sample in acetone, adding 40 mL of methanol thereto, filtering the supernatant into a 2 mL liquid chromatography vial using a 0.22 μm polytetrafluoroethylene filter, and using high performance liquid chromatography (HPLC), detecting by an evaporative light scattering detector (ELSD) according to the elution time. The peak area ratio of the biocurable resin to the epoxy resin (biocurable resin: epoxy resin) detected by an evaporative light scattering detector (ELSD) according to the elution time using high performance liquid chromatography (HPLC) can be determined based on the ratio of the biocurable resin to the epoxy resin present in the curable resin composition. In a specific embodiment, the curable resin composition can have a peak area ratio of the biocurable resin to the epoxy resin (biocurable resin:epoxy resin) detected by an evaporative light scattering detector (ELSD) using high performance liquid chromatography (HPLC) according to elution time of 0.60 or more, 0.65 or more, 0.70 or more, 0.75 or more, 0.80 or more, 0.85 or more, 0.90 or more, 0.95 or more, 1.00 or more, or 1.05 or more: 1, and 5.60 or less, 5.50 or less, 5.40 or less, 5.30 or less, 5.20 or less, 5.10 or less, 5.00 or less, 4.90 or less, 4.80 or less, 4.70 or less, 4.60 or less, 4.50 or less, or 4.40 or less. As described above, in the case where a mixed biocurable resin and an epoxy resin are used as a curable resin, if the peak area ratio of the biocurable resin to the epoxy resin (biocurable resin: epoxy resin) detected by an evaporative light scattering detector (ELSD) using high performance liquid chromatography (HPLC) according to the elution time is controlled as described above, environmental pollution can be reduced by using an environmentally friendly bio-based epoxy resin instead of a conventional petroleum-based epoxy resin, all the mechanical strength properties required of a curable resin composition containing a conventional petroleum-based epoxy resin can be met, and at the same time, the viscosity can be easily adjusted to further improve the dispersion efficiency of the graft copolymer in the curable resin, thereby further improving productivity and mechanical properties.

[0070] According to one embodiment of the present invention, curable resin can comprise 58 wt % to 82 wt % of biocurable resin and 18 wt % to 42 wt % of epoxy resin. In a specific embodiment, curable resin can comprise more than 58 wt %, more than 59 wt %, more than 60 wt %, more than 61 wt %, more than 62 wt %, more than 63 wt %, more than 64 wt % or more than 65 wt %, and less than 82 wt %, less than 81 wt % or less than 80 wt % of biocurable resin, and the epoxy resin of the remaining amount. Like this, if biocurable resin and epoxy resin are mixed and used as curable resin, then viscosity can be easily adjusted, and the dispersion efficiency of graft copolymer in curable resin can be further improved.

[0071] According to one embodiment of the present invention, the graft copolymer may include a core-shell type graft copolymer including a core including a rubbery polymer and a shell formed by graft-copolymerizing a graft monomer to the rubbery polymer.

[0072] According to one embodiment of the present invention, in the core-shell graft copolymer, the core may refer to the rubbery polymer component itself that forms the core or core layer of the graft copolymer, and the shell may refer to the polymer component or copolymer component that forms the shell or shell layer as a shell type, which is grafted polymerized to the rubbery polymer and surrounds the core. That is, the core containing the rubbery polymer may be the rubbery polymer itself, and the shell may refer to the grafted layer formed by grafting the grafted monomer to the rubbery polymer. According to one embodiment of the present invention, the rubbery polymer is a component for providing impact resistance in the case of applying the graft copolymer composition as an impact enhancer, and may include one or more monomer units selected from the conjugated diene monomer unit and the alkyl acrylate monomer unit. In a specific embodiment, the rubbery polymer may be a conjugated diene rubbery polymer or an acrylic rubbery polymer (acrylic rubberypolymer). In a more specific embodiment, the conjugated diene rubbery polymer may be one or more selected from the homopolymer of the conjugated diene monomer and the copolymer of the aromatic vinyl monomer-conjugated diene monomer, and the acrylic rubbery polymer may be a homopolymer of the alkyl acrylate monomer.

[0073] According to one embodiment of the present invention, the conjugated diene monomer of the rubbery polymer may be one or more selected from 1,3-butadiene, 2,3-dimethyl-1,3-butadiene, piperylene, 3-butyl-1,3-octadiene, isoprene and 2-phenyl-1,3-butadiene, specifically, 1,3-butadiene.

[0074] According to one embodiment of the present invention, the aromatic vinyl monomer of the rubber-like polymer can be one or more selected from styrene, α-methylstyrene, 3-methylstyrene, 4-methylstyrene, 4-propylstyrene, 1-vinylnaphthalene, 4-cyclohexylstyrene, 4-(p-methylphenyl)styrene and 1-vinyl-5-hexylnaphthalene, specifically, styrene.

[0075] According to one embodiment of the present invention, the alkyl acrylate monomer of the rubbery polymer may be an alkyl acrylate monomer of 1 to 12 carbon atoms, specifically, one or more selected from methyl acrylate, ethyl acrylate, propyl acrylate and n-butyl acrylate, more specifically, n-butyl acrylate.

[0076] According to one embodiment of the present invention, in the case of applying the graft copolymer composition as an impact reinforcing agent, the shell is a component for improving compatibility and mechanical properties, and as described above, the shell may be a graft layer formed by grafting a graft monomer to a rubbery polymer. In a specific embodiment, the graft monomer grafted to the rubbery polymer for forming the shell may include an alkyl (meth)acrylate monomer.

[0077] According to one embodiment of the present invention, the (meth)acrylic acid alkyl ester monomer of the grafting monomer can be a (meth)acrylic acid alkyl ester monomer of 1 to 12 carbon atoms, specifically, one or more selected from methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, methyl acrylate, ethyl acrylate, propyl acrylate and n-butyl acrylate.

[0078] According to one embodiment of the present invention, the (meth) acrylate alkyl monomer of the graft monomer can be a (meth) acrylate methyl monomer and a (meth) acrylate alkyl monomer of 2 to 12 carbon atoms, and in this case, the weight average molecular weight of the shell can be further reduced, so that in the process of dispersing the graft copolymer in the curable resin, the swelling of the shell can be minimized and the increase in viscosity can be prevented. In this case, the (meth) acrylate alkyl monomer can include 50% to 99% by weight, 60% to 90% by weight, or 70% to 85% by weight of a (meth) acrylate methyl monomer, and 1% to 50% by weight, 10% to 40% by weight, or 15% to 30% by weight of a (meth) acrylate alkyl monomer of 2 to 12 carbon atoms.

[0079] According to one embodiment of the present invention, in addition to the (meth) alkyl acrylate monomer, the graft monomer may further include a crosslinkable monomer. That is, the graft monomer may include a methyl (meth) acrylate monomer, an alkyl (meth) acrylate monomer of 2 to 12 carbon atoms, and a crosslinkable monomer.

[0080] According to one embodiment of the present invention, the crosslinkable monomer is simultaneously crosslinked in the process of forming the shell by the grafted monomer, thereby further improving the compatibility and mechanical properties of the shell while improving the shell forming ability, and can be one or more selected from the following: (meth)acryl-based crosslinking monomers, such as ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, allyl (meth)acrylate, trimethylolpropane tri(meth)acrylate and pentaerythritol tetra(meth)acrylate; and vinyl-based crosslinkable monomers, such as divinylbenzene, divinylnaphthalene and diallyl phthalate, specifically, polyethylene glycol diacrylate or allyl methacrylate.

[0081] According to one embodiment of the present invention, the graft monomer may further include an aromatic vinyl monomer, that is, the graft monomer may include a methyl (meth)acrylate monomer, an alkyl (meth)acrylate monomer having 2 to 12 carbon atoms, and an aromatic vinyl monomer.

[0082] According to one embodiment of the present invention, the aromatic vinyl monomer of the grafting monomer can be one or more selected from styrene, α-methylstyrene, 3-methylstyrene, 4-methylstyrene, 4-propylstyrene, 1-vinylnaphthalene, 4-cyclohexylstyrene, 4-(p-methylphenyl)styrene and 1-vinyl-5-hexylnaphthalene, specifically, styrene.

[0083] According to one embodiment of the present invention, if the grafting monomer further includes an aromatic vinyl-based monomer, the aromatic vinyl-based monomer may be included in an amount of 0.1 wt % to 10.0 wt %, 0.5 wt % to 5.0 wt % or 0.8 wt % to 2.0 wt % based on the total amount of the grafting monomer.

[0084] In the curable resin composition according to the present invention, in order to enable dispersion by a powder phase dispersion method, it may be important to control the content of the core in the graft copolymer and the particle size distribution of the core.

[0085] According to one embodiment of the present invention, the graft copolymer may include 70% to 92% by weight of the core. In a specific embodiment, the graft copolymer may include more than 70% by weight, more than 71% by weight, more than 72% by weight, more than 73% by weight, more than 74% by weight or more than 75% by weight, and less than 92% by weight, less than 91% by weight, less than 90% by weight, less than 89% by weight, less than 88% by weight, less than 87% by weight, less than 86% by weight, less than 85% by weight, less than 84% by weight, less than 83% by weight, less than 82% by weight, less than 81% by weight or less than 80% by weight of the core. Therefore, the graft copolymer can include more than 8 weight %, more than 9 weight %, more than 10 weight %, more than 11 weight %, more than 12 weight %, more than 13 weight %, more than 14 weight %, more than 15 weight %, more than 16 weight %, more than 17 weight %, more than 18 weight %, more than 19 weight % or more than 20 weight %, and less than 30 weight %, less than 29 weight %, less than 28 weight %, less than 27 weight %, less than 26 weight % or less than 25 weight % shell. Within this range, if the graft copolymer composition is dispersed in the curable resin, the increase in viscosity can be prevented by minimizing the swelling of the shell while ensuring sufficient compatibility between the curable resin and the graft copolymer composition. The content of core and shell can be derived from the content ratio of the rubbery polymer added in the process of preparing the graft copolymer to the graft monomer.

[0086] According to one embodiment of the present invention, the core may have an average particle size of 100 nm to 500 nm, specifically, an average particle size of more than 100 nm, more than 150 nm, more than 200 nm, more than 250 nm, more than 260 nm, more than 270 nm, more than 280 nm, more than 290 nm or more than 300 nm, and less than 500 nm, less than 490 nm, less than 480 nm, less than 470 nm, less than 460 nm, less than 450 nm, less than 440 nm, less than 430 nm, less than 420 nm, less than 410 nm, less than 400 nm, less than 390 nm, less than 380 nm, less than 370 nm, less than 360 nm, less than 350 nm, less than 340 nm, less than 335 nm, less than 330 nm or less than 325 nm. Within this range, in the process of dispersing the graft copolymer composition in the curable resin, aggregation between small particles can be prevented, and the reduction of dispersibility caused by increased viscosity can be prevented.

[0087] As described above, by controlling the content of the core in the plurality of graft copolymers including cores having different particle sizes included in the graft copolymer composition according to the present invention and the particle size distribution of the core, it is possible to disperse in the curable resin composition by a powder phase dispersion method.

[0088] According to one embodiment of the present invention, the weight average molecular weight of the shell may be 10,000 g / mol to 85,000 g / mol. In a specific embodiment, the weight average molecular weight of the shell can be 10,000 g / mol or more, 15,000 g / mol or more, 20,000 g / mol or more, 25,000 g / mol or more, 30,000 g / mol or more, 35,000 g / mol or more, or 40,000 g / mol or more, and 85,000 g / mol or less, 84,000 g / mol or less, 83,000 g / mol or less, 82,000 g / mol or less, 81,000 g / mol or less, 80,000 g / mol or less, 75,000 g / mol or less, 70,000 g / mol or less, 65,000 g / mol or less, 60,000 g / mol or less, 55,000 g / mol or less, 50,000 g / mol or less, 45,000 g / mol or less, or 40,000 g / mol or less. Within this range, sufficient compatibility between the curable resin and the graft copolymer can be ensured while minimizing the swelling of the shell to prevent viscosity increase during the dispersing of the graft copolymer in the curable resin. The weight average molecular weight of the shell can be adjusted by controlling the amount of an initiator, an activator, etc. added during the graft polymerization of the graft monomer in the presence of the rubbery polymer.

[0089] According to one embodiment of the present invention, the graft copolymer may have an average particle size of 100 nm to 600 nm, specifically, the average particle size is 100 nm or more, 150 nm or more, 200 nm or more, 250 nm or more, 260 nm or more, 270 nm or more, 280 nm or more, 290 nm or more, 300 nm or more, 305 nm or more, 310 nm or more, 315 nm or more, 320 nm or more, or 325 nm or more, and 600 nm or less, 590 nm or less, 580 nm or less, 570 nm or less, 560 nm or less. The graft copolymer can be dispersed in a curable resin in an amount of at least 300 nm, at least 350 nm, at least 360 nm, at least 370 nm, at least 380 nm, at least 390 nm, at least 390 nm, at least 380 nm, at least 370 nm, at least 360 nm, at least 350 nm, at least 340 nm, at least 335 nm, at least 330 nm or at least 325 nm. Within this range, an increase in viscosity can be prevented during the dispersion of the graft copolymer in the curable resin.

[0090] According to one embodiment of the present invention, the curable resin composition may include 50% to 99% by weight of a continuous phase and 1% to 50% by weight of a dispersed phase. In a specific embodiment, the curable resin composition may include more than 50% by weight, more than 51% by weight, more than 52% by weight, more than 53% by weight, more than 54% by weight, or more than 55% by weight and less than 99% by weight, less than 95% by weight, less than 90% by weight, less than 85% by weight, less than 80% by weight, less than 75% by weight, less than 70% by weight, less than 65% by weight, less than 60% by weight, or less than 55% by weight of a continuous phase. In addition, accordingly, the curable resin composition may contain 1 wt % or more, 5 wt % or more, 10 wt % or more, 15 wt % or more, 20 wt % or more, 25 wt % or more, 30 wt % or more, 35 wt % or more, 40 wt % or more or 45 wt % and 50 wt % or less, 49 wt % or less, 48 ​​wt % or less, 47 wt % or less, 46 wt % or less or 45 wt % of the dispersed phase.

[0091] Furthermore, the present invention provides a method for preparing a curable resin composition for preparing the curable resin composition.

[0092] According to one embodiment of the present invention, a method for preparing a curable resin composition includes: a step (S10) of preparing a graft copolymer latex including a graft copolymer; a step (S20) of aggregating and drying the graft copolymer latex prepared in step (S10) to prepare a graft copolymer powder; and a step (S30) of mixing a curable resin with the graft copolymer powder prepared in step (S20) to prepare a curable resin composition, wherein step (S30) is performed by dispersing using a stirrer.

[0093] According to one embodiment of the present invention, step (S10) can be carried out by comprising the following steps: a step (S1) of preparing a rubbery polymer latex including a rubbery polymer; and a step (S2) of injecting a grafting monomer and performing graft polymerization in the presence of the rubbery polymer latex to prepare a graft copolymer latex, the graft copolymer latex including a graft copolymer composition comprising a plurality of graft copolymers having a core-shell type.

[0094] According to one embodiment of the present invention, in the method for preparing a curable resin composition, the type and content of monomers used to perform the respective steps may be the same as those of the above-mentioned curable resin composition.

[0095] According to one embodiment of the present invention, step (S1) is a step of preparing a rubbery polymer for forming a core or a core layer in a core-shell type graft copolymer, and step (S2) is a step of forming a shell or a shell layer as a shell type surrounding the core by grafting the rubbery polymer.

[0096] According to one embodiment of the present invention, each of step (S1) and step (S2) can be performed by emulsion polymerization, and can be performed in the presence of an emulsifier and an initiator injected during the emulsion polymerization, as well as an electrolyte, a molecular weight regulator, an activator, etc. In this case, when performing step (S1), the particle size distribution of the rubbery polymer particles of the rubbery polymer particles can be adjusted by the added content of the emulsifier.

[0097] According to one embodiment of the present invention, the emulsifier may be one or more selected from fatty acid-based emulsifiers and rosin acid-based emulsifiers, and in this case, an excellent effect of latex stability may be obtained.

[0098] According to one embodiment of the present invention, based on 100 parts by weight of the monomer for polymerizing the rubbery polymer, the amount of the emulsifier added in step (S1) can be 0.1 parts by weight to 3.4 parts by weight, 1.0 parts by weight to 3.3 parts by weight, 1.5 parts by weight to 3.2 parts by weight, 2.0 parts by weight to 3.2 parts by weight, or 2.1 parts by weight to 3.1 parts by weight.

[0099] According to one embodiment of the present invention, based on a total of 100 parts by weight of the rubber-like polymer and the monomers for polymerizing the graft copolymer, the amount of the emulsifier added in step (S2) can be 0.1 to 1.0 parts by weight, 0.1 to 0.5 parts by weight or 0.1 to 0.3 parts by weight, and within this range, an excellent latex stability effect can be obtained.

[0100] According to one embodiment of the present invention, step (S1) can be carried out using a water-soluble initiator that can be used in the process of emulsion polymerization, and the water-soluble initiator can include potassium persulfate, sodium persulfate, ammonium persulfate, etc. Step (S2) can be carried out by using a free radical polymerization of a peroxide, redox or azo initiator that can be used in the process of emulsion polymerization, and the redox initiator can be, for example, selected from one or more of tert-butyl hydroperoxide, diisopropylbenzene hydroperoxide and cumene hydroperoxide. In this case, the effect of providing a stable polymerization environment can be obtained. If a redox initiator is used, ferrous sulfide, sodium ethylenediaminetetraacetate or sodium formaldehyde sulfoxylate can be further included as a redox catalyst, i.e. as an activator.

[0101] According to one embodiment of the present invention, step (S2) can be performed by continuously adding the grafting monomer. In performing step (S2), if the grafting monomer is added in batches before initiating the graft polymerization reaction, there may be a defect of increasing the weight average molecular weight of the shell.

[0102] According to one embodiment of the present invention, the emulsion polymerization in step (S1) and step (S2) may be performed in an aqueous solvent, and the aqueous solvent may be ion-exchanged water.

[0103] According to one embodiment of the present invention, step (S20) is a step of obtaining the graft copolymer prepared in step (S10) as a powder phase, and may be performed by aggregating and drying the graft copolymer latex prepared in step (S10).

[0104] According to one embodiment of the present invention, the aggregation in step (S20) can be carried out by adding a coagulant to the graft copolymer latex. In addition, the aggregation in step (S20) can be carried out by the aggregation of acids such as aqueous sulfuric acid and the aggregation of alkalis such as sodium sulfate, and acid aggregation and alkali aggregation can be carried out as required. In this case, acid aggregation and alkali aggregation can be carried out simultaneously or step by step. If aggregation is carried out step by step, acid aggregation can be carried out first, and then alkali aggregation can be carried out, or alkali aggregation can be carried out first, and then acid aggregation can be carried out. In addition, as required, the aggregation in step (S20) can be carried out in the presence of an organic dispersant.

[0105] According to one embodiment of the present invention, the drying in step (S20) may be performed by a conventional drying method, and may further include a step of dehydrating the aggregated graft copolymer latex before drying, as required.

[0106] According to one embodiment of the present invention, step (S30) is a step of mixing the curable resin with the graft copolymer by the above-mentioned powder phase dispersion method when the graft copolymer is applied to the curable resin as an impact reinforcing agent, and can be performed by adding the graft copolymer powder to the curable resin and mixing. As described above, the graft copolymer according to the present invention has excellent powder dispersibility and can be directly dispersed in the curable resin in the form of powder. In a specific embodiment, the viscosity of the curable resin composition prepared in step (S30) at 25°C may be 2,000 Pa.s or less, 1,900 Pa.s or less, 1,800 Pa.s or less, 1,700 Pa.s or less, 1,600 Pa.s or less, 1,500 Pa.s or less, 1,450 Pa.s or less, 1,400 Pa.s or less, 1,350 Pa.s or less, or 1,300 Pa.s or less, and 100 Pa.s or more, 200 Pa.s or more, 300 Pa.s or more, 400 Pa.s or more, 500 Pa.s or more, 600 Pa.s or more, 700 Pa.s or more, 800 Pa.s or more, 900 Pa.s or more, 1,000 Pa.s or more, 1,100 Pa.s or more, or 1,200 Pa.s or more, within this range, the graft copolymer powder has low viscosity and excellent dispersibility.

[0107] In addition, the present invention provides an adhesive composition comprising the curable resin composition. The adhesive composition may be a structural adhesive composition, and may comprise the curable resin composition as a toughening agent.

[0108] According to one embodiment of the present invention, the adhesive composition may include a main material usable in an adhesive, a polyurethane resin, and a curing agent, in addition to a toughening agent, and may further include a curing accelerator and a filler.

[0109] According to one embodiment of the present invention, the main material may include a biocurable resin, similarly to the curable resin composition. In this case, the type of the biocurable resin may be the same as that of the biocurable resin of the curable resin composition.

[0110] According to one embodiment of the present invention, based on the total content of the adhesive composition, the main material may include a biocurable resin in an amount of 1 wt % to 40 wt %. In a specific embodiment, based on the total content of the adhesive composition, the main material may include a biocurable resin in an amount of 1 wt % or more, 5 wt % or more, 10 wt % or more, 15 wt % or more, or 20 wt % or more and 40 wt % or less, 35 wt % or less, or 30 wt % or less, and within this range, the effect of the structural adhesive may be further improved.

[0111] According to one embodiment of the present invention, based on the total content of adhesive composition, adhesive composition can include content is 5 weight % to 32 weight % toughener.In a specific embodiment, based on the total content of adhesive composition, adhesive composition can include more than 5 weight %, more than 6 weight %, more than 7 weight %, more than 8 weight %, more than 9 weight % or more than 10 weight %, and below 32 weight %, below 31 weight %, below 30 weight %, below 29 weight %, below 28 weight %, below 27 weight %, below 26 weight %, below 25 weight %, below 24 weight %, below 23 weight %, below 22 weight %, below 21 weight %, below 20 weight %, below 19 weight %, below 18 weight %, below 17 weight %, below 16 weight % or below 15 weight % toughener.Within the scope, adhesive, particularly structural adhesive composition can further improve relative to the impact strength of heterogeneous adhesive.

[0112] Hereinafter, embodiments of the present invention will be described in detail so that those skilled in the art to which the present invention pertains can easily proceed. However, the present invention can be implemented in various different types and is not limited to the embodiments described herein.

[0113] Examples and Comparative Examples

[0114] Example 1

[0115] <Preparation of Rubber-like Polymer Latex>

[0116] Based on a total of 100 parts by weight of 1,3-butadiene, 75 parts by weight of ion exchange water, 60 parts by weight of 1,3-butadiene, 1.4 parts by weight of potassium rosinate, 0.6 parts by weight of potassium oleate, 0.9 parts by weight of potassium carbonate (K2CO3), 0.3 parts by weight of tert-dodecyl mercaptan and 0.3 parts by weight of potassium persulfate (K2S2O3) were added in batches to a nitrogen-substituted polymerization reactor (autoclave), and polymerization was performed at a reaction temperature of 70°C. Then, at a point where the polymerization conversion rate was 30% to 40%, 0.7 parts by weight of potassium oleate was added in batches, 20 parts by weight of 1,3-butadiene was added in batches, and polymerization was continuously performed at a reaction temperature of 70°C. Then, after the polymerization conversion rate reached 60%, 20 parts by weight of 1,3-butadiene was added in batches, the reaction temperature was raised to 80°C, the polymerization reaction was continuously performed, and the reaction was terminated at a point where the polymerization conversion rate reached 95%. The total time consumed for the polymerization was 23 hours, and the gel content of the obtained rubbery polymer latex was 76%, and the average particle size of the rubbery polymer particles was 300 nm.

[0117] In this case, the polymerization conversion rate is calculated as the ratio of the weight of the solid content of the obtained rubbery polymer to the weight of the solid content of the charged monomer.

[0118] <Preparation of Graft Copolymer Latex>

[0119] Into a nitrogen-substituted closed polymerization reactor, 75 parts by weight (based on solid content) of the rubbery polymer latex thus prepared was added, based on a total of 100 parts by weight of the rubbery polymer latex (based on solid content), methyl methacrylate, n-butyl acrylate and styrene, and 200 parts by weight of ion-exchanged water, 0.2 parts by weight of potassium oleate, 0.036 parts by weight of ferrous sulfide, 0.2 parts by weight of sodium ethylenediaminetetraacetate, 0.2 parts by weight of sodium formaldehyde sulfoxylate and 0.25 parts by weight of tert-butyl hydroperoxide were added in batches. Then, polymerization was carried out at a reaction temperature of 60° C. for 4 hours, while 18 parts by weight of methyl methacrylate, 5 parts by weight of n-butyl acrylate and 2 parts by weight of styrene were continuously added over 3 hours to prepare a graft copolymer latex.

[0120] <Preparation of Graft Copolymer Powder>

[0121] The graft copolymer latex thus prepared was diluted in distilled water to 15 wt % based on solid content and put into an aggregation bath, and then the internal temperature of the aggregation bath was raised to 45° C. Thereafter, IR1076 was added as an antioxidant to 100 parts by weight of the graft copolymer based on solid content, agglomerated while stirring was performed while adding an aqueous sulfuric acid solution, and the graft copolymer and water were separated, followed by dehydration and drying to prepare a graft copolymer powder.

[0122] <Preparation of Epoxy Resin Composition Dispersed with Graft Copolymer>

[0123] Based on a total of 100 parts by weight of the epoxy resin and the graft copolymer, 55 parts by weight of the epoxy resin and 45 parts by weight of the graft copolymer powder thus prepared were added to a planetary mixer (KMTech, KPLM-0.6) set at 70° C., and stirred at 10 rpm for 1 hour, 80 rpm for 2 hours, and 60 rpm for 10 hours to disperse the graft copolymer powder in the epoxy resin, thereby preparing an epoxy resin composition dispersed with a graft copolymer.

[0124] In this case, 65 wt % of an isosorbide-based epoxy resin (Kukdo Chemical Co., KDBM-1040; EEW = 165 g / eq–185 g / eq; 25° C. viscosity = 3,000 cPs–6,000 cPs) and 35 wt % of a bisphenol A-based epoxy resin (Kukdo Chemical Co., YD-128; EEW = 184 g / eq–190 g / eq; 25° C. viscosity = 11,500 cPs–13,500 cPs) were mixed and used as the epoxy resin.

[0125] <Preparation of Structural Adhesive Composition>

[0126] A paste mixer (KM Tech Co., PDM-300) was used to mix the following materials at 600 rpm revolution and 500 rpm rotation: 30 parts by weight of an isosorbide-based epoxy resin (Kukdo Chemical Co., KDBM-1040; EEW = 165 g / eq-185 g / eq; 25°C viscosity = 3,000 cPs-6,000 cPs) as main materials and 25.4 parts by weight of a bisphenol A-based epoxy resin (Kukdo Chemical Co., YD-128; EEW = 184 g / eq-190 g / eq; 25°C viscosity = 11,500 cPs-13,500 cPs); 15 parts by weight of the epoxy resin composition prepared above as a toughening agent; 20 parts by weight of a polyurethane resin (Adeka Co., QR-9466); 4.9 parts by weight of a curing agent (Evonik Co., Dicyanex 1400F); 0.7 parts by weight of a curing accelerator (Evonik Co., Amicure UR7 / 10); 3.0 parts by weight of calcium oxide (Youyeong Materials Co., UNI-OX); and 1.0 parts by weight of fumed silica (Carbot Co., CAB-O-SIL TS-720) were mixed for 3 minutes and defoamed at 600 rpm revolution and 200 rpm rotation for 5 minutes to prepare an adhesive composition. In this case, the curing agent was added according to the equivalent of the epoxy resin, and the curing accelerator was added at an equivalent ratio of 1 / 7 of the curing agent.

[0127] Example 2

[0128] A graft copolymer latex was prepared in the same manner as in Example 1, except that 0.5 parts by weight of potassium oleate was added instead of 0.2 parts by weight and 0.5 parts by weight of tert-butyl hydroperoxide was added instead of 0.25 parts by weight during the preparation of the graft copolymer latex in Example 1, and a graft copolymer powder was prepared.

[0129] In addition, an epoxy resin composition was prepared in the same manner as in Example 1, except that the prepared graft copolymer powder was used as the graft copolymer powder in the process of preparing the epoxy resin composition in Example 1, and an isosorbide-based epoxy resin (Kukdo Chemical Co., KDBM-1040) was used as the epoxy resin by mixing 70 wt % instead of 65 wt % and bisphenol A-based epoxy resin (Kukdo Chemical Co., YD-128) instead of 35 wt %.

[0130] Example 3

[0131] An epoxy resin composition was prepared in the same manner as in Example 1, except that 70 wt % of an isosorbide-based epoxy resin (Kukdo Chemical Co., KDBM-1040) was mixed instead of 65 wt % and 30 wt % of a bisphenol A-based epoxy resin (Kukdo Chemical Co., YD-128) was used as the epoxy resin in the process of preparing the epoxy resin composition in Example 1.

[0132] In addition, an adhesive composition was prepared in the same manner as in Example 1, except that 40 parts by weight of an isosorbide-based epoxy resin (Kukdo Chemical Co., KDBM-1040) was mixed instead of 30 parts by weight and 15.4 parts by weight of a bisphenol A-based epoxy resin (Kukdo Chemical Co., YD-128) was used as the main material in the process of preparing the structural adhesive composition of Example 1, and the same amount of the epoxy resin composition was added as a toughening agent.

[0133] Example 4

[0134] An epoxy resin composition was prepared in the same manner as in Example 1, except that 80 wt % of an isosorbide-based epoxy resin (Kukdo Chemical Co., KDBM-1040) was mixed instead of 65 wt % and 20 wt % of a bisphenol A-based epoxy resin (Kukdo Chemical Co., YD-128) was mixed instead of 35 wt % as the epoxy resin in the process of preparing the epoxy resin composition in Example 1.

[0135] In addition, an adhesive composition was prepared in the same manner as in Example 1, except that 20 parts by weight of an isosorbide-based epoxy resin (Kukdo Chemical Co., KDBM-1040) was mixed instead of 30 parts by weight and 35.4 parts by weight of a bisphenol A-based epoxy resin (Kukdo Chemical Co., YD-128) was used as a main material in the process of preparing the structural adhesive composition of Example 1, and the same amount of the prepared epoxy resin composition was added as a toughening agent.

[0136] Example 5

[0137] An epoxy resin composition was prepared in the same manner as in Example 1, except that in the process of preparing the epoxy resin composition of Example 1, 70 weight % of isosorbide-based epoxy resin (Kukdo Chemical Co., KDBM-1040) was mixed instead of 65 weight % and 30 weight % of bisphenol A-based epoxy resin (Kukdo Chemical Co., YD-128) was used as the epoxy resin, 50 weight parts of epoxy resin was added instead of 55 weight parts, and 50 weight parts of the prepared graft copolymer powder was added instead of 45 weight parts.

[0138] In addition, the adhesive composition was prepared in the same manner as in Example 1, except that 30.4 parts by weight of bisphenol A epoxy resin (Kukdo Chemical Co., YD-128) was added as the main material instead of 25.4 parts by weight during the preparation of the structural adhesive composition in Example 1, and 10 parts by weight of the prepared epoxy resin composition was added as a toughening agent.

[0139] Example 6

[0140] The rubber-like polymer latex was prepared in the same manner as in Example 1, except that 50 parts by weight of ion exchange water was added instead of 75 parts by weight, and 1.8 parts by weight of potassium carbonate (K2CO3) was added instead of 0.9 parts by weight during the preparation of the rubber-like polymer latex in Example 1, and a graft copolymer latex and a graft copolymer powder were prepared.

[0141] In addition, an epoxy resin composition was prepared in the same manner as in Example 1, except that the graft copolymer powder thus prepared was used as the graft copolymer powder in the process of preparing the epoxy resin composition in Example 1, and an isosorbide-based epoxy resin (Kukdo Chemical Co., KDBM-1040) was used as the epoxy resin by mixing 70 wt % instead of 65 wt % and 30 wt % instead of 35 wt % of a bisphenol A-based epoxy resin (Kukdo Chemical Co., YD-128). And an adhesive composition was prepared.

[0142] Example 7

[0143] A graft copolymer latex was prepared in the same manner as in Example 1, except that 90 parts by weight of the prepared rubbery polymer latex was added instead of 75 parts by weight, 7 parts by weight of methyl methacrylate was added instead of 18 parts by weight, 2 parts by weight of n-butyl acrylate was added instead of 5 parts by weight, and 1 part by weight of styrene was added instead of 2 parts by weight based on the solid content during the preparation of the graft copolymer latex in Example 1, and a graft copolymer powder was prepared.

[0144] In addition, an epoxy resin composition was prepared in the same manner as in Example 1, except that the graft copolymer powder thus prepared was used as the graft copolymer powder in the process of preparing the epoxy resin composition in Example 1, and an isosorbide-based epoxy resin (Kukdo Chemical Co., KDBM-1040) was used as the epoxy resin by mixing 70 wt % instead of 65 wt % and 30 wt % instead of 35 wt % of a bisphenol A-based epoxy resin (Kukdo Chemical Co., YD-128). And an adhesive composition was prepared.

[0145] Example 8

[0146] A graft copolymer latex was prepared in the same manner as in Example 1, except that 0.1 parts by weight of potassium oleate was added instead of 0.2 parts by weight and 0.125 parts by weight of tert-butyl hydroperoxide was added instead of 0.25 parts by weight during the preparation of the graft copolymer latex in Example 1, and a graft copolymer powder was prepared.

[0147] In addition, an epoxy resin composition was prepared in the same manner as in Example 1, except that the graft copolymer powder thus prepared was used as the graft copolymer powder in the process of preparing the epoxy resin composition in Example 1, and an isosorbide-based epoxy resin (Kukdo Chemical Co., KDBM-1040) was used as the epoxy resin by mixing 70 wt % instead of 65 wt % and 30 wt % instead of 35 wt % of a bisphenol A-based epoxy resin (Kukdo Chemical Co., YD-128). And an adhesive composition was prepared.

[0148] Example 9

[0149] The adhesive composition was prepared in the same manner as in Example 1, except that 25 parts by weight of isosorbide-based epoxy resin (Kukdo Chemical Co., KDBM-1040) were added instead of 30 parts by weight and 15.4 parts by weight of bisphenol A-based epoxy resin (Kukdo Chemical Co., YD-128) were added as main materials instead of 25.4 parts by weight during the preparation of the structural adhesive composition in Example 1, and 30 parts by weight of the prepared epoxy resin composition was added as a toughening agent.

[0150] Comparative Example 1

[0151] An epoxy resin composition was prepared in the same manner as in Example 1, except that 85 wt % of an isosorbide-based epoxy resin (Kukdo Chemical Co., KDBM-1040) was mixed instead of 65 wt % and 15 wt % of a bisphenol A-based epoxy resin (Kukdo Chemical Co., YD-128) was used as the epoxy resin in the process of preparing the epoxy resin composition in Example 1, and an adhesive composition was prepared.

[0152] Comparative Example 2

[0153] A graft copolymer latex was prepared in the same manner as in Example 1, except that 0.08 parts by weight of potassium oleate was added instead of 0.2 parts by weight and 0.100 parts by weight of tert-butyl hydroperoxide was added instead of 0.25 parts by weight during the preparation of the graft copolymer latex in Example 1, and a graft copolymer powder, an epoxy resin composition and an adhesive composition were prepared.

[0154] Comparative Example 3

[0155] A graft copolymer latex was prepared in the same manner as in Example 1, except that 0.08 parts by weight of potassium oleate was added instead of 0.2 parts by weight and 0.100 parts by weight of tert-butyl hydroperoxide was added instead of 0.25 parts by weight during the preparation of the graft copolymer latex in Example 1, and a graft copolymer powder was prepared.

[0156] In addition, an epoxy resin composition was prepared in the same manner as in Example 1, except that the graft copolymer powder thus prepared was used as the graft copolymer powder in the process of preparing the epoxy resin composition in Example 1, and an isosorbide-based epoxy resin (Kukdo Chemical Co., KDBM-1040) was used as the epoxy resin by mixing 70 wt % instead of 65 wt % and 30 wt % instead of 35 wt % of a bisphenol A-based epoxy resin (Kukdo Chemical Co., YD-128). And an adhesive composition was prepared.

[0157] Comparative Example 4

[0158] A graft copolymer latex was prepared in the same manner as in Example 1, except that 1.0 part by weight of potassium oleate was added instead of 0.2 part by weight and 0.9 part by weight of tert-butyl hydroperoxide was added instead of 0.25 part by weight during the preparation of the graft copolymer latex in Example 1, and a graft copolymer powder was prepared.

[0159] In addition, an epoxy resin composition was prepared in the same manner as in Example 1, except that the graft copolymer powder thus prepared was used as the graft copolymer powder in the process of preparing the epoxy resin composition in Example 1, and an isosorbide-based epoxy resin (Kukdo Chemical Co., KDBM-1040) was used as the epoxy resin by mixing 70 wt % instead of 65 wt % and 30 wt % instead of 35 wt % of a bisphenol A-based epoxy resin (Kukdo Chemical Co., YD-128). And an adhesive composition was prepared.

[0160] Comparative Example 5

[0161] A graft copolymer latex was prepared in the same manner as in Example 1, except that 0.7 parts by weight of potassium oleate was added instead of 0.2 parts by weight and 0.7 parts by weight of tert-butyl hydroperoxide was added instead of 0.25 parts by weight during the preparation of the graft copolymer latex in Example 1, and a graft copolymer powder was prepared.

[0162] In addition, an epoxy resin composition was prepared in the same manner as in Example 1, except that the graft copolymer powder thus prepared was used as the graft copolymer powder in the process of preparing the epoxy resin composition in Example 1, and an isosorbide-based epoxy resin (Kukdo Chemical Co., KDBM-1040) was used as the epoxy resin by mixing 70 wt % instead of 65 wt % and 30 wt % instead of 35 wt % of a bisphenol A-based epoxy resin (Kukdo Chemical Co., YD-128). And an adhesive composition was prepared.

[0163] Comparative Example 6

[0164] An epoxy resin composition was prepared in the same manner as in Example 1, except that 50 wt % of an isosorbide-based epoxy resin (Kukdo Chemical Co., KDBM-1040) was mixed instead of 65 wt % and 50 wt % of a bisphenol A-based epoxy resin (Kukdo Chemical Co., YD-128) was used as the epoxy resin in the process of preparing the epoxy resin composition in Example 1, and an adhesive composition was prepared.

[0165] Experimental Example 1

[0166] For the rubbery polymers and graft copolymers prepared in Examples 1 to 9 and Comparative Examples 1 to 6, the average particle diameters of the core and graft copolymers and the weight average molecular weight of the shell were measured and shown in Tables 1 to 3 below together with the content of each component.

[0167] *Average particle size (nm) of core and graft copolymer: Each of the rubbery polymer latex and graft copolymer latex prepared in Examples 1 to 9 and Comparative Examples 1 to 6 was diluted in distilled water to a concentration of 200 ppm and measured by a dynamic light scattering (DSL) method according to ISO 22412 using NICOMP380.

[0168] *Average molecular weight of shell (g / mol): The weight average molecular weight of the shell in the graft copolymer having a core-shell type was measured by gel permeation chromatography (GPC, PL GPC220, Agilent Technologies) under the following conditions.

[0169] In this case, a portion of the graft copolymer solution dispersed in tetrahydrofuran was taken and the precipitate was separated by centrifugation. The supernatant was taken and filtered through a 0.45 μm PTFE syringe filter and used as the sample solution. The graft copolymer standard was 30.0 mg / mL, and the linear polymer was sampled at a concentration of 1.5 mg / mL.

[0170] – Column: PL MiniMixed B×2

[0171] –Solvent: Tetrahydrofuran (stabilized with BHT)

[0172] – Flow rate: 1.0ml / min

[0173] – Sample concentration: 1.0mg / ml

[0174] – Injection volume: 100μl

[0175] – Column temperature: 30°C

[0176] – Detector: Waters 2414 Refractive Index Detector

[0177] –Data processing: Empower 3

[0178] [Table 1]

[0179]

[0180] [Table 2]

[0181]

[0182] [Table 3]

[0183]

[0184] Experimental Example 2

[0185] For the epoxy resin composition in which the graft copolymer as the curable resin composition prepared in Examples 1 to 9 and Comparative Examples 1 to 6 was dispersed, the dispersion state of the graft copolymer was confirmed by the following method, and the viscosity was measured. For some Examples and Comparative Examples, the peak area ratio of each of the biocurable resin and the epoxy resin measured using an evaporative light scattering detector of high performance liquid chromatography was calculated and shown in Tables 4 to 6 below together with the content of each component.

[0186] *Dispersion state: The epoxy resin composition was applied to a cold rolled (CR) steel sheet having a size of 25 mm×100 mm to a thickness of 0.2 mm, and the number of particles observed with the naked eye was confirmed. In this case, if the number of particles observed with the naked eye was less than 10, the dispersion state indicated good, if the number of particles was 10 to less than 50, the dispersion state indicated ordinary, and if the number of particles was 50 or more, the dispersion state indicated poor.

[0187] *25°C viscosity (Pa.s): For the epoxy resin composition prepared above, the 25°C viscosity was measured using a rheometer (Anton paar Co., MRC 302), and it was shown that at a shear rate of 2.4 s -1 And the viscosity value at 100s.

[0188] *Peak area ratio: 0.2g of the epoxy resin composition sample prepared above was dissolved in acetone, and 40mL of methanol was added thereto. Using a 0.22μm polytetrafluoroethylene (PTFE) filter, the supernatant was filtered into a 2mL liquid chromatography vial, and a high performance liquid chromatography (HPLC) was used to detect the peak areas of the biocurable resin and epoxy resin according to the elution time by an evaporative light scattering detector (ELSD). Then, the peak area ratio of the biocurable resin and epoxy resin (biocurable resin: epoxy resin) was calculated.

[0189] [Table 4]

[0190]

[0191] [Table 5]

[0192]

[0193] [Table 6]

[0194]

[0195] As shown in Tables 4 and 5, all the curable resin compositions of Examples 1 to 9 prepared according to the present invention exhibited excellent dispersion states and 25° C. viscosities of 960 to 1,900 Pa.s, and it can be confirmed that the dispersion states were excellent despite being dispersed in a powder phase.

[0196] In contrast, as shown in Table 6, the curable resin composition prepared in Comparative Example 1 was prepared in a non-flowable gel state rather than a flowable liquid of a dispersion, and therefore, it was confirmed that the graft copolymer was not dispersed in the powder phase.

[0197] Furthermore, it was confirmed that the dispersibility of the curable resin compositions prepared in Comparative Examples 2 and 3 was reduced because the shell having high affinity with the epoxy resin swelled due to the high weight average molecular weight of the shell.

[0198] Furthermore, it was confirmed that the dispersion state of the curable resin compositions prepared in Comparative Examples 4 and 5 was degraded because the compatibility was not sufficiently secured due to the low weight average molecular weight of the shell.

[0199] Furthermore, it was confirmed that the dispersibility of the curable resin composition prepared in Comparative Example 6 was rather reduced because the content of the epoxy resin was increased to the same content as that of the biocurable resin.

[0200] Experimental Example 3

[0201] For the structural adhesive compositions prepared in Examples 1 to 9 and Comparative Examples 1 to 6, shear strength and impact peel strength were measured by the following methods and are shown in Tables 7 to 9 below together with the content of each component.

[0202] * Shear strength (lap shear, MPa): The shear strength of the structural adhesive composition prepared according to ASTM D1002 standard measurement. The size of the specimen is 180mm x 25.4mm x 1.6T (mm), and the size of the side on which the adhesive composition is applied is 25.4mm x 12.5mm. After removing contaminants from one side of the specimen using ethanol, the structural adhesive composition prepared is applied. Microbeads are used to keep the thickness of the adhesive composition constant, another sample is covered and fixed on the top, and then cured at 180 ℃ for 30 minutes. After curing, shear strength is measured by applying a load at a rate of 1.3mm / min using a UTM tester (Instron Co., 5900).

[0203] * Impact peel strength (N / mm): The impact peel strength of the structural adhesive composition prepared above was measured according to ISO 11343 standards. The size of the specimen was 90mm x 20mm x 1.6T (mm), and the size of the side on which the adhesive composition was applied was 30mm x 20mm. After removing contaminants from one side of the specimen using ethanol, the structural adhesive composition prepared was applied. Microbeads were used to keep the thickness of the adhesive composition constant, and another sample was covered and fixed on the top, and then cured at 180°C for 30 minutes. After curing, at 25°C and -40°C, respectively, more than 1 hour of stabilization was performed, and the impact peel strength according to shear strength was measured by applying a load at a rate of 2mm / second using an impact strength tester (Instron Co., 9350).

[0204] [Table 7]

[0205]

[0206] [Table 8]

[0207]

[0208] [Table 9]

[0209]

[0210] As shown in Tables 7 and 8, it can be confirmed that all structural adhesive compositions of Examples 1 to 9 including the curable resin composition prepared according to the present invention as a toughening agent and a biocurable resin as a main material exhibited excellent shear strength and impact peel strength.

[0211] In contrast, as shown in Table 9, it can be confirmed that in the structural adhesive composition prepared using the curable resin composition of Comparative Example 1, in which an excessive amount of the biocurable resin is used in the curable resin in the process of preparing the curable resin composition, the graft copolymer is not dispersed in the curable resin composition, and both the shear strength and the impact peel strength are reduced.

[0212] Furthermore, in the case of Comparative Examples 2 and 3 in which the weight average molecular weight of the shell of the graft copolymer of the dispersed phase was high, it was confirmed that, in the structural adhesive composition prepared using the curable resin composition, the graft copolymer was not dispersed in the curable resin composition, and both the shear strength and the impact peel strength were reduced.

[0213] In addition, in the case of Comparative Examples 4 and 5 in which the weight average molecular weight of the shell of the graft copolymer of the dispersed phase was low, it was confirmed that, in the structural adhesive composition prepared using the curable resin composition, the dispersion state of the graft copolymer in the curable resin composition was poor, and both the shear strength and the impact peel strength were reduced.

[0214] In addition, in the structural adhesive composition prepared using the curable resin composition of Comparative Example 6, wherein the same amount of biocurable resin and epoxy resin were used in the curable resin during the preparation of the curable resin composition, it was confirmed that the graft copolymer was not dispersed in the curable resin composition, and both the shear strength and the impact peel strength were reduced.

[0215] It can be confirmed from the results that the curable resin composition of the present invention reduces environmental pollution by using environmentally friendly bio-based resins instead of traditional petroleum-based epoxy resins, while satisfying all the mechanical strength properties required of the curable resin composition containing traditional petroleum-based epoxy resins, and the graft copolymer is dispersed in the curable resin by a powder phase dispersion method, resulting in excellent productivity and excellent mechanical properties.

[0216] Furthermore, the adhesive composition of the present invention is a structural adhesive composition and is excellent in mechanical strength while including an environmentally friendly bio-based epoxy resin as a main material by applying a curable resin composition as a toughening agent.

Claims

1. A curable resin composition comprising a continuous phase containing a curable resin and a dispersed phase containing a graft copolymer, in, The curable resin comprises 58 wt % to 82 wt % of a biocurable resin and 18 wt % to 42 wt % of an epoxy resin, The graft copolymer is a core-shell type graft copolymer including a core including a rubbery polymer and a shell formed by graft-polymerizing a grafting monomer to the rubbery polymer, The shell has a weight average molecular weight of 10,000 g / mol to 85,000 g / mol.

2. The curable resin composition according to claim 1, wherein The biocurable resin is a bioepoxy resin.

3. The curable resin composition according to claim 1, wherein The biocurable resin comprises isosorbide units.

4. The curable resin composition according to claim 1, wherein The biocurable resin is represented by the following formula 1: [Formula 1] In formula 1, R 1 and R 2 are each independently hydrogen, hydroxy, epoxy or glycidyl, n is an integer selected from 1 to 1,000.

5. The curable resin composition according to claim 1, wherein The biocurable resin has an epoxy equivalent weight (EEW) of 150 g / eq to 190 g / eq.

6. The curable resin composition according to claim 1, wherein The biocurable resin has a 25° C. viscosity of 500 cps to 6,000 cPs.

7. The curable resin composition according to claim 1, wherein The epoxy resin includes one or more selected from bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol AD ​​epoxy resin, bisphenol E epoxy resin, naphthalene epoxy resin, biphenyl epoxy resin, dicyclopentadiene epoxy resin, phenol novolac epoxy resin, aliphatic cyclic epoxy resin and glycidylamine epoxy resin.

8. The curable resin composition according to claim 1, wherein The epoxy resin has an epoxy equivalent weight (EEW) of 180 g / eq to 190 g / eq.

9. The curable resin composition according to claim 1, wherein The epoxy resin has a 25° C. viscosity of 8,000 cPs to 13,500 cPs.

10. The curable resin composition according to claim 1, wherein The peak area ratio of the biocurable resin to the epoxy resin (biocurable resin: epoxy resin) is 0.60 to 5.60:1, and the peak area ratio is obtained as follows: 0.2 g of the curable resin composition sample is dissolved in acetone, 40 mL of methanol is added thereto, the supernatant is filtered into a 2 mL liquid chromatography vial using a 0.22 μm polytetrafluoroethylene filter, and high performance liquid chromatography (HPLC) is used to detect by an evaporative light scattering detector (ELSD) according to the elution time.

11. The curable resin composition according to claim 1, wherein The rubbery polymer includes one or more monomer units selected from conjugated diene-based monomer units and alkyl acrylate-based monomer units.

12. The curable resin composition according to claim 1, wherein The core has an average particle size of 100 nm to 500 nm.

13. The curable resin composition according to claim 1, wherein The grafting monomer includes an alkyl (meth)acrylate monomer.

14. The curable resin composition according to claim 1, wherein The grafting monomer includes a methyl (meth)acrylate monomer and an alkyl (meth)acrylate monomer having 2 to 12 carbon atoms.

15. The curable resin composition according to claim 1, wherein The grafting monomer includes an aromatic vinyl monomer.

16. The curable resin composition according to claim 1, wherein The graft copolymer includes 70 to 92 wt % of the core and 8 to 30 wt % of the shell.

17. The curable resin composition according to claim 1, wherein The graft copolymer has an average particle size of 100 nm to 600 nm.

18. The curable resin composition according to claim 1, wherein The curable resin composition includes 50 to 99 wt % of the continuous phase and 1 to 50 wt % of the dispersed phase.

19. An adhesive composition comprising the curable resin composition according to any one of claims 1 to 18.

Citation Information

Patent Citations

  • Thermosetting resin composition and its use

    JP2006104328A